2002
DOI: 10.1016/s0014-5793(02)02369-4
|View full text |Cite
|
Sign up to set email alerts
|

SufC hydrolyzes ATP and interacts with SufB from Thermotoga maritima

Abstract: Genetic experiments in bacteria have shown the suf operon is involved in iron homeostasis and the oxidative stress response. The sufB and sufC genes that always occur together in bacteria are also found in plants, and even the malaria parasite, associated with the plastid organelle. Although the suf operon is believed to encode an iron-dependent ABC-transporter there is no direct evidence. By immunolocalization we show here that SufB and SufC are associated with the membrane of Escherichia coli. We also presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
66
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 21 publications
4
66
0
1
Order By: Relevance
“…In fact, the individual SufB, SufC, and SufD proteins could only be completely separated from the complex using reverse phase high performance liquid chromatography, indicating tight association. This result is consistent with previous yeast two-hybrid (27) and fluorescence anisotropy (26) studies that suggest interactions between SufC and the SufB and SufD proteins. The SufBCD complex was in a folded conformation based on its CD spectra and also possessed ATPase activity (data not shown).…”
Section: Purification Of the Suf Proteins-thesupporting
confidence: 93%
See 2 more Smart Citations
“…In fact, the individual SufB, SufC, and SufD proteins could only be completely separated from the complex using reverse phase high performance liquid chromatography, indicating tight association. This result is consistent with previous yeast two-hybrid (27) and fluorescence anisotropy (26) studies that suggest interactions between SufC and the SufB and SufD proteins. The SufBCD complex was in a folded conformation based on its CD spectra and also possessed ATPase activity (data not shown).…”
Section: Purification Of the Suf Proteins-thesupporting
confidence: 93%
“…SufA is a homologue of IscA and can form Fe-S clusters in vitro (25). SufC has the sequence hallmarks of the ATPase subunit of ABC transporters and has been shown to exhibit ATPase activity (26). The biochemical functions of SufB, SufD, and SufE are unknown, although fluorescence anisotropy and yeast two-hybrid assays indicate that SufB and SufD interact with SufC (26,27).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The suf operon (sufABCDSE) represents the third Fe-S system, and recent studies have shown that Suf proteins are involved in Fe-S cluster biosynthesis and repair. SufB, SufC, and SufD are conserved in nature, and in bacteria SufC interacts with SufB and SufD in the cytosol (17,18). SufE interacts with SufS, involved in cysteine desulfuration (6), and SufA assembles Fe-S clusters transiently in vitro (19).…”
mentioning
confidence: 99%
“…Bacterial SufC can hydrolyze ATP and probably acts as an energizer for the Suf system (6,17,18). SufC represents an ATP-binding cassette (ABC) protein with no membranespanning domains (18), implying that it is soluble, although conflicting evidence suggests that SufC may be membranelocalized in E. coli (17).…”
mentioning
confidence: 99%